The Mapping of Tax Compliance Research in Indonesia - Risca Novita Sari; Nurul Herawati; Nur Farahah Mohd Pauzi (Wahana Riset Akuntansi, 2023)
Purpose – This study aims to review the development of tax research, especially tax compliance in Indonesia for 22 years. Design/methodology/approach – The review is based on 129 tax compliance articles published in Indonesian accredited scientific journals Science and Technology Index (Sinta)  1 and 2 and/or A and B in 2001 – 2022. Tax compliance articles were selected with the keywords “tax compliance,” “tax non-compliance,” “tax compliance taxpayer," and "taxpayer compliance." Article mapping includes journal names, publication years, research methods, research variables, research data sources, and research tax subjects.Findings – This study found that the development of taxpayer compliance research tends to increase from year to year and most of all in 2019. Most of the publications of taxpayer compliance articles are in the journal Accounting Analysis Journal. Most of the taxpayer compliance articles use quantitative methods and primary data sources. Research with quantitative methods more often use variables of taxpayer compliance, quality of tax services, and tax sanctions. The most researched tax subject is the individual taxpayer.Originality/value – This study provides evidence of the development of tax compliance research in Indonesia in the field of accounting which has been published in national scientific journals accredited SINTA 1 and 2 and/or A and B for over two decades. It maps all tax compliance articles published in the SINTA 1 and 2 and/or A and B indexing portals without any restrictions related to the publication year. SINTA 1 and 2 and/or A and B were used in the review because the Science and Technology Index (SINTA) is a popular national portal as a reference in scientific research and has been accredited by ARJUNA (National Journal Accreditation). This current research furthers prior studies by using additional keywords for the article search. This study used three Indonesian keywords “kepatuhan pajak,” “ketidakpatuhan pajak,” “kepatuhan wajib pajak,” and on English keyword “taxpayer compliance” in the search.Research limitations/implications – The findings can be used as material for evaluating researchers’ performance in the field of tax accounting, especially on tax compliance. Findings also provide information regarding the tax compliance research trend in Indonesia and serves as a useful reference for further research, especially for research on related topic. In this research, the sensitivity of the keywords is the research limitation.